Online Marketing Strategy in a Sharia Economic Perspective - Wulandari, Sri Rahayu; Hasriadi, Hasriadi (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The goal of this study is to investigate Diniya Sunnah Style Boutique's online marketing approach from a Sharia economic perspective to boost sales of Muslim clothing. The nature of this research is descriptive data obtained through descriptive research methods. Data obtained through interview, observation, documentation, and analysis of data obtained qualitatively is concluded using inductive thinking. The research results show that the marketing strategy implemented by Diniya Sunnah Style Boutique uses a marketing mix strategy that includes product strategy, price strategy, place strategy, and promotion strategy. Promotional strategies and product strategies are very influential in increasing sales at Diniya Sunnah Style Boutique. The online marketing strategy for Diniya Sunnah Style Boutique is following the greeting agreement of posting pictures including clear product specifications, and this of course increases consumer confidence in Diniya Sunnah Style Boutique.